Evaluating undesired scratching in domestic cats: a multifactorial approach to understand risk factors - Demirbas, Yasemin Salgirli; Pereira, Joana Soares; De Jaeger, Xavier; Meppiel, Laurianne; Endersby, Sarah; da Graça Pereira, Gonçalo (Frontiers in Veterinary Science, 2024)
Introduction Despite being a natural feline behavior, scratching can become undesirable from a human perspective when directed at household items. This complex behavior can stem from various motivations, ranging from individual cat characteristics to environmental factors. This study investigates the factors influencing the increased level of undesirable scratching behavior in domestic cats, considering both cat-related and environmental aspects. Methods Data from 1,211 cats were collected for this study. An online questionnaire comprising three sections was utilized. The first section gathered caregiver demographics, while the subsequent section examined aspects of cats’ daily routines, social interactions, environments, behaviours, and temperaments. The final section assessed the frequency and intensity of undesirable scratching behavior in cats. Scratching behavior was evaluated based on a combined scratching index. Results The study suggests that the presence of a child may be associated with scratching episodes in the home environment. Additionally, factors such as play duration, playfulness, and nocturnal activity were identified as significant contributors to heightened scratching levels (p ≤ 0.05). Aggressiveness and disruptiveness also played significant roles in increased scratching behavior (p ≤ 0.05). The location of scratching posts emerged as a significant factor, with posts placed in areas frequented by the cat being more effective in redirecting scratching behavior (p ≤ 0.05). Discussion This study reveals several significant associations between cat characteristics, nocturnal activity and play, as well as the environment. It underscores the multifaceted nature of undesirable scratching behavior and emphasizes the importance of comprehensively understanding both the individual characteristics of the cat and its environment to effectively address this behavior.